2020
DOI: 10.1080/10408398.2020.1821598
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thermal processing on the nutrients, phytochemicals, and metal contaminants in edible algae

Abstract: Edible algae products have increasingly become a larger component of diets worldwide. Algae can be a source of essential micronutrients and bioactive phytochemicals, although select varieties also often contain elevated concentrations of heavy metal contaminants. Due to the effects thermal processing of foodstuffs can have on levels of nutrients, phytochemicals, and contaminants, it is important to consider the role processing has on the levels of these components in algae food products. Here, we evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 156 publications
1
16
0
1
Order By: Relevance
“…With regards to human safety, crustacean shells may play an important role in As accumulation. While shells are not considered an edible part of seafood, shellfish is often prepared for consumption with shells intact, and should be considered as some studies suggest the potential conversion of organic arsenic into iAs following thermal processing or gastrointestinal digestion (Ho & Redan, 2020; Liao et al., 2018) thus leading to a potentially higher exposure.…”
Section: Resultsmentioning
confidence: 99%
“…With regards to human safety, crustacean shells may play an important role in As accumulation. While shells are not considered an edible part of seafood, shellfish is often prepared for consumption with shells intact, and should be considered as some studies suggest the potential conversion of organic arsenic into iAs following thermal processing or gastrointestinal digestion (Ho & Redan, 2020; Liao et al., 2018) thus leading to a potentially higher exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Brown seaweeds commonly have an unacceptable high concentration of iodine which may be reduced by up to 94% by boiling for a few minutes. However, boiling causes loss of flavonoids and water-soluble nutrients which limits the prevalence [116].…”
Section: Thermal Processingmentioning
confidence: 99%
“…The effects of thermal processing on the quality properties of seaweeds in terms of bioactive substances (Amorim et al, 2012), nutritional components (Maehre et al, 2015), metal pollutants (Ho & Redan, 2020), and flavors (Sanchez-Garcia et al, 2020) have been reported. However, the color and texture as two main indicators are used to evaluate the quality of instant laver products, which are influenced by the composition of raw materials and processing parameters.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…There are many pigments in laver, and the change in color may be related to the degradation of pigments during heating(Tello-Ireland et al, 2011). The color of algae was mainly determined by the composition and content of chlorophyll, phycocyanin, and PE(Ho & Redan, 2020). In order to explore the reasons for the change of color under different circumstances, changes in pigment of laver during heating were summarized in Table2.…”
mentioning
confidence: 99%